The family health strategy as object of health education - Besen, Candice Boppré; Netto, Mônica de Souza; Da Ros, Marco Aurélio; Silva, Fernanda Werner da; Silva, Cleci Grandi da; Pires, Moacir Francisco (Saúde e Sociedade, 2007)
This study investigated whether the proposal of the Family Health Strategy (FHS) is discussed with the population in the educational practice of the professionals inserted in this strategy, and the understanding of Health Education that these professionals have. It is a qualitative, exploratory-descriptive research, carried out through semi-structured interviews. The content analysis identified the following categories: Health Education; The University does not teach; and FHS as Object of Health Education. The results showed that FHS is not an object of education; some professionals are unaware of its principles and the majority of them has vertical educational practices based on diseases, which makes them distance themselves from the proposal of Health Promotion of the FHS. The study provides reflections on the conceptions of Health Education that pervade the discourse of the professionals, as well as on their participation in the community qualification for the construction of autonomy, citizenship and health determinants control in the Health Promotion perspective. The article points to the importance of Permanent Education and to the reorganization of undergraduate studies, so that the Health Education practice is closer to the social reality.